Kepercayaan Masyarakat Terhadap Pengobatan Komplementer Akupuntur di Praktik Perawat Mandiri Latu Usadha Abiansemal Badung: Public Trust in Acupuncture as Complementary Medication in Private Nurse Latu Usadha Clinic Abiansemal Badung - Ariyanti, Kadek Sri; Sariyani, Made Dewi; Pemayun, Cokorda Istri Mita (Stikes Wira Medika Bali, 2021)
Background: Complementary therapy is a form of non-conventional medication or treatment that comes from various systems, modalities and health care practices based on theory and belief. Non-conventional treatments are often successful when the conventional ones are unsuccessful and have mild side effects that can be detrimental to the patient. Acupuncture is a complementary therapy that works as an effort to optimize health services. Specifically, acupuncture is a method of treatment by inserting needles into acupuncture points of the body. In regards to planning and identifying the care needed by patients, it is necessary to study how public trust in acupuncture as complementary medication more deeply. Objective: This study examines how public trust are built in complementary acupuncture medication. Methods: This study uses qualitative methods. The instrument used is an in-depth interview. Data collection was carried out in March-May 2020. The informants in this study were 10 patients who did acupuncture therapy. Additionally, informants were selected randomly (randomization). In regards to assess the informants' experience, researchers used a Likert scale. Findings and discussion: Results and Discussion: The majority of the informants had very good experience with acupuncture treatment. Some internal factors that influence people's trust in applying complementary acupuncture medication are belief / tradition, perception and knowledge, while the external factors are economical, culture, employment, income and family support. Conclusions and Suggestions: Promotion and development of complementary health services for acupuncture can be done more effectively and innovatively. Thus, people are provided with options of the health services they prefer.